Alethic Pluralism and the Role of Reference in the Metaphysics of Truth. Issue 1 (March 2017) - Ball, Brian
Abstract: In this paper, I outline and defend a novel approach to alethic pluralism, the thesis that truth has more than one metaphysical nature: where truth is, in part, explained by reference, it is (relevantly) relational in character and can be regarded as consisting in correspondence; but where instead truth does not depend upon reference it is not (relevantly) relational and involves only coherence. In the process, I articulate a clear sense in which truth may or may not depend upon reference: this involves distinguishing semantic denotation from pragmatic speaker reference and claiming that there may or may not exist a metasemantic connection between these two notions. Finally, I argue that reference is not in general inscrutable—that this metasemantic connection does exist in the case of our ordinary discourse about present macroscopic concrete objects—but that it is in pure mathematics, where reference cannot be secured, and which therefore plays no role in accounting for truth. In this manner, alethic pluralism is upheld.